The Milk Biochemical Parameters and Sucking Behaviour of Lambs until 35 d of Age - CIMEN, M. (Asian Journal of Chemistry, 2010)
The object of the experiment was to investigate the effect of lactation weeks on sucking behaviour and milk biochemistry until 35 d of age and find the correlations between sucking parameters and biochemical milk components. Ten Karayaka male lambs were used in the present studies. Sucking parameters of each lamb were observed at 7, 14, 21, 28 and 35 d of age. It was found the significant differences in fat levels of milk between first and last three periods of experiment. Urea-N and protein levels of milk were stable throughout the study. Milk intake of lambs declined (p < 0.05) significantly as the lamb age increased from 7 to 14 d. There were significant differences between first and last three periods in median duration of sucking bouts of lambs (p < 0.05). Total duration of sucking bouts of lambs decreased (p < 0.05) significantly as the lambs increased from 7 to 14 d. The number of sucking bouts gradually declined from 7 to 35 d and the differences between 7 and all other d are significant (p < 0.05). Median duration of sucking bouts was significantly correlated with milk intake (r = 0.33, p < 0.05) and milk fat (r = 0.29, p < 0.05). There was a significant correlation (r = 0.29, p < 0.05) between total duration of sucking bouts and milk intake. The urea-N and protein in milk have no significant effect on lamb sucking behaviour.